Contribution of specific residues of the β-solenoid fold to HET-s prion function, amyloid structure and stability. - Asen Daskalov (Public Library of Science (PLoS), 2014)
The [Het-s] prion of the fungus Podospora anserina represents a good model system for studying the structure-function relationship in amyloid proteins because a high resolution solid-state NMR structure of the amyloid prion form of the HET-s prion forming domain (PFD) is available. The HET-s PFD adopts a specific β-solenoid fold with two rungs of β-strands delimiting a triangular hydrophobic core. A C-terminal loop folds back onto the rigid core region and forms a more dynamic semi-hydrophobic pocket extending the hydrophobic core. Herein, an alanine scanning mutagenesis of the HET-s PFD was conducted. Different structural elements identified in the prion fold such as the triangular hydrophobic core, the salt bridges, the asparagines ladders and the C-terminal loop were altered and the effect of these mutations on prion function, fibril structure and stability was assayed. Prion activity and structure were found to be very robust; only a few key mutations were able to corrupt structure and function. While some mutations strongly destabilize the fold, many substitutions in fact increase stability of the fold. This increase in structural stability did not influence prion formation propensity in vivo. However, if an Ala replacement did alter the structure of the core or did influence the shape of the denaturation curve, the corresponding variant showed a decreased prion efficacy. It is also the finding that in addition to the structural elements of the rigid core region, the aromatic residues in the C-terminal semi-hydrophobic pocket are critical for prion propagation. Mutations in the latter region either positively or negatively affected prion formation. We thus identify a region that modulates prion formation although it is not part of the rigid cross-β core, an observation that might be relevant to other amyloid models.